Native forest conversion alters soil macroinvertebrate diversity and soil quality in tropical mountain landscapes of northern Ecuador - Guarderas, Paulina; Trávez, Kerly; Boeraeve, Fanny; Cornelis, Jean-Thomas; Dufrêne, Marc (Frontiers in Forests and Global Change, 2022)
Land use changes cause soil degradation and loss of biodiversity, thereby affecting ecological processes and soil-associated ecosystem services. However, land use change impacts on soil health have received little attention in the highland landscapes of the tropics, such as the remnant and threatened montane forests of Andean landscapes. In this research, using the soil health framework, we assessed the impact of native forest conversion to anthropic systems (planted forests, pastures, and monocultures) on soil fertility and biodiversity conservation in the highlands of northern Ecuador. The biological dimension of our assessment focused on the diversity, abundance, and biomass of edaphic macroinvertebrate communities as proxies to soil functions. The soil invertebrate communities and soil chemical parameters were studied in topsoil samples using 25×25×10 cm monoliths, obtained from ten sampling sites randomly selected in each land use category. We hypothesized that native forests would present more diverse and even edaphic macrofaunal communities, and together with their soil chemical properties would indicate better soil quality to support ecosystem services related to soil conservation and fertility than anthropic environments. Our results showed that the structure and composition of the edaphic macroinvertebrate communities significantly differed among the studied land use categories. As predicted, native forests presented greater values for richness, evenness and diversity of soil macroinvertebrate communities than did the other categories, demonstrating a significant loss of taxonomic biodiversity at order and genus levels. We also found a significant reduction of trophic diversity in native forests converted to anthropic environments. More trophic groups with greater abundances were found in native forests, where predators and detritivores stood out as dominant groups, indicating the good quality of the soil. The results from the soil chemical parameters also confirmed the distinction in soil health between native forests and anthropic environments. Our results highlight the risk associated with current trends of native forest loss and conversion to managed systems in high mountain ecosystems in the tropics, illustrating how these alterations could cause biodiversity loss and degradation of the chemical attributes of soil health.